الجملة الإنشائية في اللغتين العربية والإندونيسية في ضوء التحليل التقابلي (جملة النهي مثالاً): Comparative Study of Arabic and Indonesian in Prohibition Sentences - Rustam Koly (البصيرة: مجلة الدراسات الإسلامية, 2022)
This study aims to determine Arabic and Indonesian grammar in the form of prohibition sentences, by discussing the similarities and differences between them, after describing their respective grammars to find out where the difficulties of Indonesian students in learning Arabic, especially in prohibition sentences. This study uses a comparative research methodology through three research steps, namely: (1) to describe prohibited sentences in Arabic and Indonesian grammar; (2) collect the similarities and differences in the prohibition sentences in Arabic and Indonesian grammar; (3) predicting the difficulties of students in learning Arabic due to grammatical differences between Arabic and Indonesian. The results of this study indicate that the two languages ​​have similarities in: 1) prohibition and its era, where the prohibition sentence in both languages ​​is addressed to the interlocutor, for the present or future time; 2) the prohibition sentence using only one tool "لا", "don't"; 3) this prohibition tool is always before the prohibition sentence; 4) does not require adjustments between prohibition tools and prohibition sentences, both on the type and number of objects. The grammatical differences between these two languages ​​lie in the breadth of Arabic in the variety of method and suitability in type (male or female), number, and personal (speaker, interlocutor and spoken to) where this is a difficulty for Indonesian students in learn Arabic.